Efektivitas Daily Monitoring and Evaluation Management (DIANA) Dalam Meningkatkan Kinerja Karyawan Divisi Airport Learning Center PT Angkasa Pura II (Persero) - Siti Bunga Nurjanah; Nida Handayani (Sekolah Tinggi Agama Buddha Nalanda, 2023)
The implementation of the Daily Monitoring and Evaluation Management (DIANA) program is a program for measuring employee performance per day or measuring employee productivity by comparing the realization of the completion of the tasklist that has been determined with the enactment of work pattern arrangements launched in 2020 addressed to all employees of PT Angkasa Pura II. This study aims to determine how the Effectiveness of Daily Monitoring and Evaluation Management (DIANA) in Improving the Performance of Employees of the Airport Learning Center Division of PT Angkasa Pura II (Persero). The method used is a qualitative method with data collection through interviews, observations and documentation studies. The results of the research on the accuracy of the program target are employees of PT Angkasa Pura II (Persero), but there are still employees who do not fill in the official task list / tasklist and also there are still system problems that cause illegibility of tasklist submissions to superiors so that attendance and daily performance achievements of employees are constrained. Program socialization has been carried out thoroughly even though it is online due to the pandemic situation. The purpose of the program is appropriate because it is considered capable of helping employees in doing work and becoming more measurable. Program monitoring has not been effective because program monitoring is only carried out at the beginning of the program, and there are no strict sanctions for employee indiscipline in filling out the tasklist.